Pancreatic involvement in cystic fibrosis - (:unkn) unknown (EDIZIONI MINERVA MEDICA, 2016)
Cystic fibrosis (CF) is an important genetic disorder that usually manifests in early childhood. Better understanding and improved care of CF patients in our current practice with pancreatic enzyme replacement therapy and nutritional support has enabled physicians to see them more frequently from any age groups. After the lungs, pancreas is the most important organ involved with CF. Its most frequently affected component is the exocrine pancreas while endocrine functions may also be deranged. Parenchymal damage as acute or chronic pancreatitis may also develop. Herein, we aimed to outline the types of the disease, clinical picture, diagnosis and genetic aspect of the CF linked with the pancreatic involvement.
Keywords: Cystic fibrosis; Exocrine pancreatic insufficiency; Pancreatitis; TRANSMEMBRANE CONDUCTANCE REGULATOR; FECAL ELASTASE-1; PULMONARY-FUNCTION; PHENOTYPE CORRELATIONS; BICARBONATE SECRETION; EXOCRINE PANCREAS; CHANGING FACE; MURINE MODEL; LUMINAL PH; GENE